2021
DOI: 10.1111/jace.18032
|View full text |Cite
|
Sign up to set email alerts
|

Topological hardening through oxygen triclusters in calcium aluminosilicate glasses

Abstract: Calcium aluminosilicate (CAS) glass systems are industrially significant due to their favorable optical, mechanical, and thermal properties, as well as serving as a basis for many glasses in nuclear waste confinement and alkali-free display substrates. [1][2][3][4] The properties which make them industrially desirable are closely linked to their complex structure. In general, the glass system is comprised of network forming silica and alumina units, both ideally in tetrahedral arrangement with four bonded oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Rare-earth titanate glasses generally exhibit 1.9 ≤ ≤ 2.1 4 , so the EPSR-predicted would suggest more O-Ti 3 than previously reported. A significant fraction of these triclusters, a term first used for O linking three Al-O 4 tetrahedra in aluminosilicate networks 32 , 33 , leads to topological hardening and lower glass-forming ability, similar to networks containing large fractions of Al 2 O 3 34 or TiO 2 35 . In the cases of pure Al 2 O 3 or TiO 2 , the large fraction of triclusters prevents glass formation via melt-quenching, though amorphous forms can be prepared by other means 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Rare-earth titanate glasses generally exhibit 1.9 ≤ ≤ 2.1 4 , so the EPSR-predicted would suggest more O-Ti 3 than previously reported. A significant fraction of these triclusters, a term first used for O linking three Al-O 4 tetrahedra in aluminosilicate networks 32 , 33 , leads to topological hardening and lower glass-forming ability, similar to networks containing large fractions of Al 2 O 3 34 or TiO 2 35 . In the cases of pure Al 2 O 3 or TiO 2 , the large fraction of triclusters prevents glass formation via melt-quenching, though amorphous forms can be prepared by other means 36 .…”
Section: Resultsmentioning
confidence: 99%
“…48 It has also been suggested by Ren et al 14 that the excess NBOs observed at R = 1 linearly correlate with the percentage of triclusters in the system. Recent reports by Welch et al 15 suggested that this correlation extends to peraluminous compositions in which excess charge (instead of excess NBOs) follows a linear correlation with the percentage of triclusters for the CAS system.…”
Section: 4mentioning
confidence: 86%
“…In contrast, MD studies in the literature show increasing support that the percentage of [5] Al is minimal (less than ∼3%) in both the peraluminous and metaluminous region ranging from R = 0.067 to R = 2. 2, 15,48,55,69,70 These recent works have a stronger emphasis on using computational approaches which have inherent disadvantages such as the high quench rate and the use of empirical interatomic potentials. Numerous studies have focused on examining different potential forms by comparing simulated structural features with results from neutron diffraction with excellent agreement being found.…”
Section: Discussion and Implications For Future Glass Designmentioning
confidence: 99%
See 2 more Smart Citations